2007
DOI: 10.1128/jb.00985-07
|View full text |Cite
|
Sign up to set email alerts
|

A Conserved Glycine Residue of Trimeric Autotransporter Domains Plays a Key Role inYersiniaAdhesin A Autotransport

Abstract: The Yersinia adhesin A (YadA) is a trimeric autotransporter adhesin of enteric yersiniae. It consists of three major domains: a head mediating adherence to host cells, a stalk involved in serum resistance, and an anchor that forms a membrane pore and is responsible for the autotransport function. The anchor contains a glycine residue, nearly invariant throughout trimeric autotransporter adhesins, that faces the pore lumen. To address the role of this glycine, we replaced it with polar amino acids of increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
91
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 68 publications
(101 citation statements)
references
References 45 publications
3
91
0
3
Order By: Relevance
“…Indeed a recent study showed that although the Sec machinery greatly enhances the partitioning of α-helical transmembrane segments into a lipid bilayer, insertion efficiency is influenced by the nonpolar surface area of individual amino acid side chains (37). Moreover, although the generality of our results remains to be determined, it is noteworthy that the mutation of a conserved glycine residue in the β domain of a trimeric autotransporter also appears to affect its membrane insertion (38). Thus, the efficient assembly of at least closely related classes of OM proteins may depend on the ability of the polypeptide to pack tightly or to remain flexible at specific locations.…”
Section: Discussionmentioning
confidence: 65%
“…Indeed a recent study showed that although the Sec machinery greatly enhances the partitioning of α-helical transmembrane segments into a lipid bilayer, insertion efficiency is influenced by the nonpolar surface area of individual amino acid side chains (37). Moreover, although the generality of our results remains to be determined, it is noteworthy that the mutation of a conserved glycine residue in the β domain of a trimeric autotransporter also appears to affect its membrane insertion (38). Thus, the efficient assembly of at least closely related classes of OM proteins may depend on the ability of the polypeptide to pack tightly or to remain flexible at specific locations.…”
Section: Discussionmentioning
confidence: 65%
“…There are at least two possible explanations for this phenotype; because we know that autotransporter-mediated adhesion is very much a dosedependent effect (28,29), the protein expression level of IntHA453 might be reduced compared with Int WT. Alternatively, the IntHA453 is expressed at wild type levels, but it is either masked or misfolded and thus not able to adhere to the Tir receptor.…”
Section: Intha453 Is Expressed At the Wild Type Level And The ␤-Barrementioning
confidence: 99%
“…We previously replaced G389 with the four naturally occurring residues (A, S, T, and N) and also with H in order to explore the upper size limit of the pocket. The side chain size of the residues increases in the order G Ͻ A Ͻ S Ͻ T Ͻ N Ͻ H, and polarity increases in the order A Ͻ G Ͻ S Ͻ T Ͻ N Ͻ H. When expressed in E. coli, these G389 substitutions were shown to influence YadA surface display and stability, to different degrees (19).…”
mentioning
confidence: 99%
“…We previously showed that YadA and most other known TAAs have a G residue in the second beta-strand of the membrane anchor domain which forms the beta-barrel translocator pore; in the exceptional TAAs, it is either A, S, T, or N (19). This residue (G389 in YadA of Y. enterocolitica O:8) faces the lumen of the beta-barrel.…”
mentioning
confidence: 99%